Green synthesis of CdS/NixSy nanoparticles as a route towards sustainable and scalable photocatalysts. Issue 2 (6th December 2022) - Sakizadeh, John; Cline, Joseph P.; Wolfe, Eva; Thorpe, Ryan; Snyder, Mark A.; Kiely, Christopher J.; McIntosh, Steven
Abstract : If hydrogen evolution photocatalysis are to be deployed at industrial scale, the synthesis of these photocatalytic materials must be both economically and environmentally scalable. Abstract : If hydrogen evolution photocatalysis are to be deployed at industrial scale, the synthesis of these photocatalytic materials must be both economically and environmentally scalable. This suggests that we must move towards green synthesis of earth-abundant photocatalysts while also maintaining high catalytic performance. Herein, we present the enzymatically driven, aqueous phase, low temperature, synthesis of an earth-abundant nickel sulfide (Ni x S y ) hydrogen evolution cocatalyst, and its integration into a CdS/Ni x S y heterostructured photocatalyst. This resulting photocatalyst provides hydrogen evolution rates (10 500 μmol h −1 g −1 ) comparable to photocatalysts prepared by more traditional routes. Furthermore, the Ni x S y is demonstrated to provide similar activity enhancement to the more traditional, but also more expensive platinum cocatalysts. To achieve this result, we carefully studied and engineered the synthesis environment to maintain enzyme activity towards HS − production while sustaining a sufficient concentration of free Ni 2+ in solution to enable reaction and formation of Ni x S y . Ultimately, this work provides a methodology to control the coordination of metal precursors in low temperature, aqueous systems to allow for precipitation of catalytically active materials and demonstrates the viability of green synthesis pathways for photocatalysts.